Health awareness among Emirati family - Alomosh, Ahmad Falah; Al Gharaibeh, Fakir; Alrahoomi, Salama; Nicola, Amal (Al-Adab Journal, 2019)
This study aims to identify the level of health awareness among Emirati family by identifying the most important health problems suffered by the UAE society and the extent of people’s interest in folk medicine as well as the role of cultural and social patterns in increased health problems. This study also aims to investigate the social responsibility to the citizens about their care for their health and their sense of responsibility towards it and learn about the dietary habits and lack of exercise.